Insomnia management in Dutch general practice: a routine care database study - Mette H. Bakker; Nina A. Oldejans; Jacqueline G. Hugtenburg; Henriëtte E. van der Horst; Pauline Slottje (Taylor & Francis Group, 2023)
AbstractObjective To explore insomnia management in general practice, with a focus on sleep medication prescription.Design Descriptive analysis of anonymized routine general practice care data extracted from electronic medical records (EMRs), including demographics, free text annotations from sleep consultations and sleep medication prescriptions covering one year before up to two years after the registration of the International Classification for Primary Care (ICPC) code P06 'Sleep disturbance'.Setting Twenty-one general practices in an urban area of the Netherlands.Patients Adults (18-85 year) with a first sleep consultation with their GP.Outcomes Documented non-pharmacological and sleep medication treatment.Results Of the 1,089 patients who consulted their general practitioner (GP) for sleep disturbance for the first time, about 50% had one more sleep consultation during the two years follow-up. Over two years including the first consultation, GPs documented a non-pharmacological intervention for 48.4% of the patients and prescribed sleep medication to 77.0%. 64.6% of the patients received a sleep medication prescription in the first consultation. Among patients receiving medication (N = 838); 59.6% received more than one prescription; 76.8% received one or more short-acting benzodiazepine receptor agonist (BZRA), 39.5% one or more unrecommended drugs and 14.7% >180 pills of BZRAs in two years.Conclusion Although the guidelines advocate non-pharmacological treatment and warn against unwarranted sleep medication, it is still very common in Dutch general practice to prescribe medication, even at the first sleep consultation. Prescriptions frequently include unrecommended and off-label drugs or repeated BZRA prescriptions.